Jonas Laužikas – the Initiatior of ‘Teaching and Upbringing’ of the Disabled in Lithuania - Barkauskaitė, Marijona; Šadauskas, Vilius (Pedagogika, 2018)
The life and activities of Jonas Laužikas, the Professor’s pedagogical heritage is one of the most significant theoretical sources in the history of education. His life has also served as an example for the educational reform undertaken in 1991, after the Restoration of the Lithuanian Independence, aimed at the guidelines to anticipate and address the structural, content and process changes by stopping the soviet process of fragmentation and differentiation and advocating consolidation through ‘the spread of the unifying and integrating principle’. The present article discusses the ideas and works of Jonas Laužikas who initiated the ‘teaching and upbringing’ of disabled children in response to the principle of ‘holistic education’. The aim of the study was to reveal the efforts and scientific work of Jonas Laužikas in consolidating the systematic ‘teaching and upbringing’ of disabled children. The methodology of the research is based on the analysis of the texts of the Professor Laužikas and his students’ and former colleagues’ opinions as well as the evaluation of the Teacher’s scientific heritage and the example of the personality for the past and present state education. The qualitative research was based on the content analysis method. The attitude and scientific pedagogical activity of Laužikas have opened up and expanded new directions in the pedagogy of Lithuania: experimental, social, defectological, therapeutic, as well as of special pedagogy and psychology. The use of the adapted and original research methods by the Professor and his contribution to teaching of these methods to the scientists of the Baltic States makes it possible to name him not only as a pedagogue who initiated the education of disabled children, but also as the initiatior of the pedagogical psychological methodology in Lithuania, as well as the developer and creator of research methodologies and tests, the initiator of the complex studies during which his practical pedagogical ideas were implemented. Summarizing all that has been observed, learned, studied, and experienced by personally communicating, and using the contrastive content analysis method, we can conclude that Prof. Jonas Lauzikas’ scientific work and his chosen ‘straight line of ‘middle path’ of life’ with the scientific, theoretical and practical pedagogical heritage, established the concept of ‘the holistic education of a person’, was not only ahead of his times but also transferred it to the modern system of education. In 1931, a special school was founded on the initiative of the Professor in Kaunas, where he worked as a teacher and carried out academic research. This gives J. Laužikas the status of the initiator of the education of disabled people in Lithuania. The protocoles prepared by J. Laužikas for teaching and upbringing disabled children show for the contemporary education policy makers and the educational community how much there is still left to do in education.